The compounding effect of having HIV and a disability on child mortality among mothers in South Africa. - Ilhom Akobirshoev; Hussaini Zandam; Allyala Nandakumar; Nora Groce; Mark Blecher; Monika Mitra (PLoS ONE)
Background Previous research on the association between maternal HIV status and child mortality in sub-Saharan Africa was published between 2005-2011. Findings from these studies showed a higher child mortality risk among children born to HIV-positive mothers. While the population of women with disabilities is growing in developing countries, we found no research that examined the association between maternal disability in HIV-positive mothers, and child mortality in sub-Saharan Africa. This study examined the potential compounding effect of maternal disability and HIV status on child mortality in South Africa. Methods We analyzed data for women age 15-49 years from South Africa, using the nationally representative 2016 South Africa Demographic and Health Survey. We estimated unadjusted and adjusted risk ratios of child mortality indicators by maternal disability and maternal HIV using modified Poisson regressions. Results Children born to disabled mothers compared to their peers born to non-disabled mothers were at a higher risk for neonatal mortality (RR = 1.80, 95% CI:1.31-2.49), infant mortality (RR = 1.69, 95% CI:1.19-2.41), and under-five mortality (RR = 1.78, 95% CI:1.05-3.01). The joint risk of maternal disability and HIV-positive status on the selected child mortality indicators is compounded such that it is more than the sum of the risks from maternal disability or maternal HIV-positive status alone (RR = 3.97 vs. joint RR = 3.67 for neonatal mortality; RR = 3.57 vs. joint RR = 3.25 for infant mortality; RR = 6.44 vs. joint RR = 3.75 for under-five mortality). Conclusions The findings suggest that children born to HIV-positive women with disabilities are at an exceptionally high risk of premature mortality. Established inequalities faced by women with disabilities may account for this increased risk. Given that maternal HIV and disability amplify each other's impact on child mortality, addressing disabled women's HIV-related needs and understanding the pathways and mechanisms contributing to these disparities is crucial.